2008
DOI: 10.3354/dao02006
|View full text |Cite
|
Sign up to set email alerts
|

First report of spontaneous chytridiomycosis in frogs in Asia

Abstract: This is the first report of amphibian chytridiomycosis in Asia. We discovered a lethal outbreak in Japan, among 45 exotic frogs from 18 species kept for breeding by a private owner. Of these 45 frogs, 16 died and another 7 were found to be infected by chytrid fungus Batrachochytrium dendrobatidis (Bd) but survived after treatment. Bd was detected in frogs from 9 species (Lepidobatrachus laevis, Ceratophrys cornuta, C. cranwelli, C. ornata, C. calcarata, Chacophrys pierotti, Occidozyga lima, Leptodactylus penta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…McLeod et al (2008) revealed that Batrachochytrium dendrobatidis was not found in amphibians in Thailand in the last 60 yr. Rowley et al (2007) also reported a negative result for the disease in 274 individuals of 4 native amphibian species and 137 imported amphibians in Hong Kong. The first case of B. dendrobatidis in Asia was reported in Japan among 45 exotic frogs of 18 species kept for breeding by a private owner (Une et al 2008). At the same time, B. dendrobatidis was detected in 4 samples from Rhacophorus javanus, Rana chalconota, Leptobrachium hasseltii, and Limnonectes microdiscus in Indonesia (Kusrini et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…McLeod et al (2008) revealed that Batrachochytrium dendrobatidis was not found in amphibians in Thailand in the last 60 yr. Rowley et al (2007) also reported a negative result for the disease in 274 individuals of 4 native amphibian species and 137 imported amphibians in Hong Kong. The first case of B. dendrobatidis in Asia was reported in Japan among 45 exotic frogs of 18 species kept for breeding by a private owner (Une et al 2008). At the same time, B. dendrobatidis was detected in 4 samples from Rhacophorus javanus, Rana chalconota, Leptobrachium hasseltii, and Limnonectes microdiscus in Indonesia (Kusrini et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…However, direct evidence of human-mediated movement of Bd has, until recently, been lacking. Surveillance data also show that Bd has probably been introduced recently in Dominica (Garcia et al 2007), the UK (Cunningham et al 2005), New Zealand (Bell et al 2004), Hawaii (Beard & O'Neill 2005), Japan (Une et al 2008), Sardinia (Bovero et al 2008) and Mallorca (Walker et al 2008).…”
Section: New Introductionsmentioning
confidence: 99%
“…Infection with Batrachochytrium dendrobatidis has been reported in additional captive populations around the world (Berger et al 1999, Longcore et al 1999, Mazzoni et al 2003, Une et al 2008, Marantelli et al 2004, Schloegel et al 2009). Many zoological institutions are currently involved in the captive breeding of amphibians for species re-introduction programs.…”
Section: Literature Reviewmentioning
confidence: 97%